Biotechnologies and Biomimetics for Civil Engineering - Pacheco Torgal, F (Springer, 2015)
Putting forward an innovative approach to solving current technological problems faced by human society, this book encompasses a holistic way of perceiving the potential of natural systems. Nature has developed several materials and processes which both maintain an optimal performance and are also totally biodegradable, properties which can be used in civil engineering.